2022
DOI: 10.1021/acsomega.2c01414
|View full text |Cite
|
Sign up to set email alerts
|

ESIPT-Active 8-Hydroxyquinoline-Based Fluorescence Sensor for Zn(II) Detection and Aggregation-Induced Emission of the Zn(II) Complex

Abstract: A D−π–A type quinoline derivative, 2-(((4-(1, 2, 2-triphenylvinyl)phenyl)imino)methyl)quinolin-8-ol ( HL ), was synthesized and structurally characterized. The five-membered ring formed by the O–H···N hydrogen bond in HL contributed to the excited-state intramolecular proton transfer (ESIPT) behavior of HL , which was further verified by theoretical computations. Upon coordination with Zn 2+ , the hydroxyl proton in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 57 publications
0
11
0
1
Order By: Relevance
“…The complete quenching of fluorescence in the solid 8hq is explained by the ESIPT process resulting from the formation of intramolecular O–H⋯N hydrogen bonding. 67 Therefore, creating an intermolecular ionic system capable of facilitating charge transfer between its constituent units is impossible. In the 8hq salts, the fluorescence is associated with the electron transition from lone electron pairs of the respective halide anions (chlorides or bromides) to the antibonding π orbital of 8hqH + , which further undergoes relaxation (Table 2, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The complete quenching of fluorescence in the solid 8hq is explained by the ESIPT process resulting from the formation of intramolecular O–H⋯N hydrogen bonding. 67 Therefore, creating an intermolecular ionic system capable of facilitating charge transfer between its constituent units is impossible. In the 8hq salts, the fluorescence is associated with the electron transition from lone electron pairs of the respective halide anions (chlorides or bromides) to the antibonding π orbital of 8hqH + , which further undergoes relaxation (Table 2, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4, both the DLS and SEM results revealed that the particle size reduced with increasing water content from 85% to 95%, which agreed with many reported AIE systems. 16 Fluorescence enhancement in this phase could be explicated by restricting intramolecular rotations (RIR) in the aggregates of HL . HL displayed distinct orange fluorescence in the solid state (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…They have drawn much attention in the field of fluorescence sensing owing to their superior photostabilities. [16][17][18][19] Most AIEgens exhibit "always bright" or even brighter in aqueous media because of their aggregation in aqueous solutions. This optical signal amplification effect makes them suitable for constructing "turn-off" fluorescence probes.…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al 48 synthesized D-p-A type probe 20 for Zn 2+ sensing with ESIPT-active and acceptor 8-hydroxyquinoline group and TPE group as the electron donor group (Fig. 15(i)).…”
Section: Minireviewmentioning
confidence: 99%